La Chinafrique en contextes universitaires - David Bel; Valentin Feussi (Recherches en didactique des langues et des cultures)
The term Chinafrica is nowadays widely used and refers to relationships between China and Africa, especially in the economic field. With this article, the two authors question the academic dimension of this relation. Based on their academic situations and life experiences and interviews conducted in China and Cameroon, they bring out an unexpected encounter with francophonie. However numerous issues are at stake, from political influence to opportunity effects regarding actors in various situations.